2012
DOI: 10.1002/chem.201200020
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Synthesis of Near‐Infrared Absorbing, “Push–Pull”, Bisthiophene‐Substituted, Zinc(II) Phthalocyanines and their Application in Dye‐Sensitized Solar Cells

Abstract: Zinc(II) phthalocyanine dyes that contain triarylamine-terminated bisthiophene and hexylbisthiophene groups have been synthesized by a convergent approach by using carboxytriiodo-ZnPc as a precursor. Further transformation of the iodo groups by a Pd-catalyzed reaction allowed easy preparation of further extended π-conjugated carboxy-ZnPcs. These dyes have been used as sensitizers in dye-sensitized solar cells, which exhibit a panchromatic response and moderate overall efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…Moreover, Zn-triPcNc-5 additionally presents a broad absorption band between 400 and 500 nm, which is also assigned to S atoms instead of O atoms in the six peripheral substituents of Zn-tri-PcNc-4 [19]. It is similar to the previous report that a broad absorption around 400e500 nm can be observed when the three peripheral tert-butyl groups of TT1 are replaced by the p-conjugated bisthiophene substituents [19].…”
Section: Dye Spectroscopic Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, Zn-triPcNc-5 additionally presents a broad absorption band between 400 and 500 nm, which is also assigned to S atoms instead of O atoms in the six peripheral substituents of Zn-tri-PcNc-4 [19]. It is similar to the previous report that a broad absorption around 400e500 nm can be observed when the three peripheral tert-butyl groups of TT1 are replaced by the p-conjugated bisthiophene substituents [19].…”
Section: Dye Spectroscopic Characteristicssupporting
confidence: 88%
“…As we know, the electron density on the S atom is greater than that on the O atom, the S atoms instead of O atoms in their six peripheral substituents can improve the electron density over the whole ZnPc molecule, and therefore Zn-tri-PcNc-5 shows an obvious redshift (up to~28 nm) in the Qband and significant enhancement in the molar extinction coefficient as compared to Zn-tri-PcNc-4 [17,18]. Moreover, Zn-triPcNc-5 additionally presents a broad absorption band between 400 and 500 nm, which is also assigned to S atoms instead of O atoms in the six peripheral substituents of Zn-tri-PcNc-4 [19]. It is similar to the previous report that a broad absorption around 400e500 nm can be observed when the three peripheral tert-butyl groups of TT1 are replaced by the p-conjugated bisthiophene substituents [19].…”
Section: Dye Spectroscopic Characteristicsmentioning
confidence: 98%
“…However, this efficiency is generally lower those of TT1 and other tert-butyl substituted phthalocyanine dyes [29e31]. Similar results were reported by Ince et al for ZnPc dye 2 with 5'-hexyl-2,2'-bithiophene groups [24]. It was indicated that the efficiency was increased to 2.70% by changing the electrolyte and by using coadsorbent chenodeoxycholic acid (CDCA).…”
Section: Resultssupporting
confidence: 60%
“…The Soret band was observed due to the transitions from the deeper p levels to the LUMO. ZnPc-2 additionally presents an absorption band between 400 and 550 nm, which is related to the peripheral, pconjugated, bisthiophene substituent [24]. The fluorescence spectra of phthalocyanines were presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9 Thus, a 4:1 molar ratio mixture of 3-iodophthalonitrile (2) 10 and 4-hdroxymethylphthalonitrile (3) 11 was reacted at reflux in DMAE in the presence of ZnCl2. The desired A3B ZnPc 4 was obtained in 32% yield after isolation by column chromatography (Scheme 1).…”
mentioning
confidence: 99%